The power of love: from feminist utopia to the politics of imperceptibility in Sarah Hall's fiction. Issue 4 (21st April 2019) - Cottrell, Anna
ABSTRACT: This article explores the fiction of the contemporary British writer Sarah Hall and argues that the evolution of her work centres on its changing treatment of love. Hall's perceptive engagements with British regionalism, contemporary politics, and feminism are to be read in the context of her insights into the trials and complexities of interpersonal relationships, with which her central characters tend to struggle. Her latest novel The Wolf Border (2015) is a case in point: it is both a work explicitly about contemporary Britain and one in which all of the central 'issues' are rendered decidedly peripheral, secondary to the main character's transformative experience of love. The thematic shifts require a re-thinking of literary form. Hall's abandonment of genre fiction, with which she experimented in her feminist dystopia The Carhullan Army (2007), in favour of the looser forms of her more recent work, has allowed her to focus on the significance of indecision, indeterminacy, and imperceptible change.